Matej Slekovec kot pisec posvetno-zgodovinskih del - Hozjan, Andrej (Časopis za zgodovino in narodopisje, 2024)
The article first provides an overview of the basics of the census work of the Slovenian intellectual, priest, amateur historian, and writer of local history, Matej Slekovec (1846-1903). Initially, he spent many years transcribing information from preserved materials in parishes and in rare archives – from documents and various other individual sources to parish chronicle records. This is followed by a more detailed presentations of some of the most important editions of books and scientific articles with secular-historical content, published during his lifetime and even after his death. He wrote about almost everything, about a wide variety of topics and events in eastern Slovenian Styria throughout the centuries, as well of personal biographies and biographies of noble families. With his comprehensive opus, Slekovec had a reputation and respect among the then-few Slovenian intellectuals.
Keywords: domoznanstvo; famous persons; historiography; local history; North-Eastern Slovenia; severovzhodna Slovenija; Slekovec, Matej; zgodovinopisje; znamenite osebnosti